CONSUMER PERCEPTION AND BUYING DECISION FOR INDONESIAN COSMETICS PRODUCT IN MANADO - Korengkeng, Marchella R. E.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The cosmetics industry now is more global than ever and the cosmetics consumers continues to increase in popularity over time. Cosmetics has come with all kinds of variaety to suit their facial features, starts from primer with foundation, lipstick, mascara, eyeliner and eyeshadow, eyebrows pencil, etc. There are many international companies also that produce cosmetics as their main products like Maybeline, Loreal, Revlon, and there are brands from Indonesia as well like Wardah, Purbasari, Sari Ayu. Consumers usually have perceptions about the final result of their make up work. With those perceptions, they can make evaluations to better increase their future work in doing their make up work. The purpose of this research is to know the perceptions of cosmetics cosnumers towards the products that they are using, in this case the products is local products produce by Indonesian cosmetics companies. The variety of cosmetic products is good enough for them, especially since they considered that the materials are made from all natural resources that it can be good for their skin. They also stated that the price is affordable that it really helps them in fulfilling thier needs and wants..Keywords: Consumer Perception, Buying Decision